Helen Keller : facing her challenges, challenging the world - Benge, Janet, 1958-; Benge, Geoff, 1954-; James, Kennon (Houston, TX : Advance Pub., 2000)
The life of the woman who graduated from college with honors and traveled around the world on behalf of the physically handicapped even though she had been blind and deaf since early childhood.
Keywords: Keller, Helen, -- 1880-1968 -- Juvenile literature; Sullivan, Annie, -- 1866-1936 -- Juvenile literature; Keller, Helen, -- 1880-1968.; Sullivan, Annie, -- 1866-1936.; Deafblind women -- United States -- Biography -- Juvenile literature; Deafblind people -- United States -- Biography -- Juvenile literature; Blind; Deaf people; People with disabilities; Women -- Biography